Relationship between activities of daily living in the home and functional fitness testing in youth with Down syndrome - Cossio Bolaños, Marco (2025)
Introduction. Introduction: An adequate level of functional fitness (FF) is important for quality of life and health. Objective. To determine the relationship between activities of daily living (ADL) and FF in young people with Down syndrome (DS). Methods. Fifty-nine young people with DS were evaluated for weight and height. Three FA tests were administered [handgrip strength (HGS), sit-to-stand test, and 2.44 m agility test]. ADLs were assessed using a scale. Results. The relationships between BMI and the agility test were negative. The relationship between HGS and the sit-to-stand test was positive. Young people with lower BMI had better ADL levels, and those with high ADL levels showed better HGP and performance in the agility and sit-to-stand tests. Conclusión. Better ADL levels are associated with better muscle strength and agility.